The Transcriptomic and Bioinformatic Characterizations of Iron Acquisition and Heme Utilization in Avibacterium paragallinarum in Response to Iron-Starvation - Huo, Caiyun; Zeng, Ximin; Xu, Fuzhou; Li, Fangbing; Li, Donghai; Li, Guiping; Hu, Zhenguo; Hu, Yanxin; Lin, Jun; Sun, Huiling (Frontiers in Microbiology, 2021)
Avibacterium paragallinarum, the causative agent of infectious coryza, is a highly contagious respiratory disease of chickens that brings a potentially serious threat to poultry husbandry. Iron is an essential micronutrient for most bacteria and is obtained from iron-chelating siderophores, hemophores or host-molecule-binding proteins. To date, the mechanisms of iron acquisition and haem utilization as well as detailed regulation in Av. paragallinarum have been poorly understood. In this study, we investigated the transcriptomic profiles in detail and the dynamic change of transcriptomes induced by iron-restriction in Av. paragallinarum using RNA-seq. Compared with iron-sufficiency control group, many more diﬀerentially expressed genes (DEGs), cellular functions and signaling pathways were confirmed in iron-restriction group. Among these DEGs, the majority of genes showed the decreased expression and some were found to be uniquely present in iron-restriction group. With an in-depth study of bioinformatic analyses, we demonstrated the crucial roles of Hut protein and DUF domain-containing proteins, which were preferentially activated in bacteria following iron-restriction and contributed to the iron acquisition and haem utilization. Consequently, RT-qPCR results further verified the iron-related DEGs and were consistent with the RNA-seq data. In addition, several novel sRNAs were present in Av. paragallinarum and had potential regulatory roles in iron homeostasis, especially in the regulation of Fic protein to ensure stable expression. This is the first report of the molecular mechanism of iron acquisition and haem utilization in Av. paragallinarum from the perspective of transcriptomic profiles. The study will contribute to better understanding of the transcriptomic response of Av. paragallinarum to iron-starvation, and also provide novel insight into the development of new antigens for potential vaccines against infectious coryza by focusing on these iron-related genes.